Dimensional parameters and structural topology integrated design method of a planar 5R parallel machining robot. (September 2022) - Wang, Meng; Song, Yimin; Lian, Binbin; Wang, Panfeng; Chen, Kaixuan; Sun, Tao
Highlights: An IDM of dimensional parameters and structural topology is proposed. A machinability processing algorithm is developed to meet the manufacturability. The stiffness obtained by the IDM is almost twice that of the PDM under the same mass. Abstract: Dimensional parameters and structural topology have crucial impacts on the performance of robots. However, they are disjointed from each other in the design phase. To fill this gap, an integrated design method (IDM) of dimensional parameters and structural topology is proposed. The experiment is designed with dimensional parameters and mass retention ratio as variables. The topology optimization of components is implemented for minimum compliance. Then, a machinability processing algorithm is developed to make components satisfy the manufacturability. The stiffness matrix of each component is extracted by the finite element analysis (FEA) software, and the stiffness–mass metamodel is established by the response surface method (RSM). Finally, the performance models and optimization model are built, and the stiffness–mass metamodels are embedded in them. The optimization is conducted by particle swarm optimization (PSO) algorithm. A planar five-rotational joint (5R) parallel machining robot is considered to verify the effectiveness and superiority of the proposed method. Results indicate that the stiffness obtained by the proposed approach is approximately double that obtained by the parametric design method (PDM).